Law through the life course - Herring, Jonathan (Bristol, UK : Bristol University Press, 2021)
This book is the first to explore the interactions of the law with the life course in order to understand the complex life journey as a whole. Jonathan Herring reveals how the law privileges 'middle age' to the detriment of the whole life story and explains why an understanding of the life course is important for lawyers.
Title from publisher's bibliographic system (viewed on 05 Jan 2022).
Keywords: Law; Life cycle, Human